LIN28 upregulation in primary human T cells impaired CAR T antitumoral activity - Garcia-Rodriguez, Patricia; Hidalgo, Laura; Rodriguez-Milla, Miguel Angel; Somovilla-Crespo, Beatriz; Garcia-Castro, Javier (Frontiers in Immunology, 2024)
LIN28, a highly conserved RNA-binding protein that acts as a posttranscriptional modulator, plays a vital role in the regulation of T-cell development, reprogramming, and immune activity in infectious diseases and T-cell-based immunotherapies. LIN28 inhibit the expression of let-7 miRNAs, the most prevalent family of miRNAs in lymphocytes. Recently it has been suggested that let-7 enhances murine anti-tumor immune responses. Here, we investigated the impact of LIN28 upregulation on human T cell functions, focusing on its influence on CAR T cell therapy. LIN28 lentiviral transduction of human T cells led to a stable expression of LIN28 that significantly downregulated the let-7 miRNA family without affecting cell viability or expansion potential. LIN28 overexpression maintained human T cell phenotype markers and functionality but impaired the antitumoral cytotoxicity of NKG2D-CAR T cells both in vitro and in vivo. These findings highlight the intricate relationship between LIN28/let-7 axis and human T cell functionality, including in CAR T cell therapy.